Optimization of Binder Percentage in Organic Waste-Based Briquettes: Impact on Calorific Value and Combustion Rate - Muliani, Muliani; Pangga, Dwi; Ahzan, Sukainil (Lensa: Jurnal Kependidikan Fisika, 2024)
This research focuses on optimizing the binder percentage in organic waste-based briquettes to improve their calorific value and combustion rate. Conducted through experimental methods, organic waste such as sawdust, dry leaves, and branches were processed into briquettes using varying concentrations of tapioca starch as a binder (10%, 12.5%, 15%, and 17.5%). The experiment evaluated key performance metrics, including calorific value, combustion rate, moisture content, ash content, and briquette density. Results showed that the optimal calorific value (9,234 cal/g) was achieved with 10% binder, while the highest combustion rate (0.586 g/min) occurred at 15% binder concentration. These findings suggest that lower binder percentages result in higher energy efficiency, while higher binder content prolongs combustion. However, increased binder content also led to higher ash production, with the highest ash content recorded at 17.5% binder. The research highlights that balancing the binder ratio is essential for creating briquettes that are both energy-efficient and environmentally sustainable, offering a viable alternative to traditional fuels in Indonesia's pursuit of renewable energy solutions.